2018
DOI: 10.3389/fpls.2018.00110
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Extreme Phenotype Bulk Copy Number Variation (XP-CNV) Identified the Association of rp1 with Resistance to Goss's Wilt of Maize

Abstract: Goss's wilt (GW) of maize is caused by the Gram-positive bacterium Clavibacter michiganensis subsp. nebraskensis (Cmn) and has spread in recent years throughout the Great Plains, posing a threat to production. The genetic basis of plant resistance is unknown. Here, a simple method for quantifying disease symptoms was developed and used to select cohorts of highly resistant and highly susceptible lines known as extreme phenotypes (XP). Copy number variation (CNV) analyses using whole genome sequences of bulked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 69 publications
1
23
1
Order By: Relevance
“…4 a). One NLR gene cluster on chromosome 10 has 16 genes homologous to the rp1 gene that confers resistance to common rust [ 27 ] and was associated with Goss’s wilt resistance [ 28 ] (Fig. 4 b).…”
Section: Resultsmentioning
confidence: 99%
“…4 a). One NLR gene cluster on chromosome 10 has 16 genes homologous to the rp1 gene that confers resistance to common rust [ 27 ] and was associated with Goss’s wilt resistance [ 28 ] (Fig. 4 b).…”
Section: Resultsmentioning
confidence: 99%
“…4a). One NLR gene cluster on chromosome 10 has 16 genes homologous to the rp1 gene that confers resistance to common rust 22 and was associated with Goss's wilt resistance 23 (Fig. 4b).…”
Section: Gene Annotationmentioning
confidence: 99%
“…Subsequent studies identified regions, and even genes, that confer resistance to the three most significant fungal foliar diseases – southern corn leaf blight (SCLB), northern corn leaf blight (NCLB), and gray leaf spot (GLS) ( Lopez-Zuniga et al 2019 ; Zwonitzer et al 2010 ; Belcher et al 2012 ; Yang et al 2017b ). Relatively few regions have been identified that confer resistance to both a fungal and a bacterial pathogen in maize ( Chung et al 2010 ; Chung et al 2011 ; Qiu et al 2020 ; Jamann et al 2014 ; Jamann et al 2016 ; Hu et al 2018 ). In this study, we focused on two bacterial diseases bacterial leaf streak (BLS) and Goss’s bacterial wilt and blight (GW), as well as three fungal diseases: SCLB, NCLB, and GLS.…”
mentioning
confidence: 99%